Space, art activities and the German language - Plivelić, Marijana (Rethinking childhood II: child and space, 2026)
The modern methodical approach in working with children of preschool age advocates interdisciplinary and cross-subject linking of the content of the educational process, as well as the inclusion of informal forms of teaching, for the purpose of high-quality, open, flexible and spontaneous acquisition of a foreign language. Successful acquisition of a foreign language is possible when it is based on learning about things that interest and capture the child’s attention. Since visual language is universal, spontaneous and close to the child, it represents a good basis for acquiring new words in a foreign language—German. In order to connect the contents of art culture with the contents of the German language, it is necessary to use creative visual stimuli and activities in which the child is to connect aesthetic sensibility with intuitive perception and intellectual analysis. The above encourages diversity of thinking and agency by the child, which then creates the basis for further educational processes. By integrating visual non-verbal language through various activities, the child as a co-creator in the creative process adopts the planned linguistic content in German.